HEALTH SERVICE EFFICIENCY: COST ANALYSIS OF TIME DRIVEN ACTIVITY BASED COSTING METHODS IN CAESAR SURGERY SERVICES IN PKU MUHAMMADIYAH HOSPITAL, YOGYAKARTA - Faizal Satria Desitama; Muhammad Alhada Fuadilah Habib (BALANCE: JOURNAL OF ISLAMIC ACCOUNTING, 2023)
Negative difference between the fee for cesarean surgery services provided by the hospital and the tariff claimed by BPJS resulted in the hospital bearing the cost difference. This study aims to determine the level of inefficiency in cesarean surgery healthcare services through cost calculation using the Time Driven Activity Based Costing (TDABC) method at PKU Muhammadiyah Yogyakarta Hospital. This study uses a qualitative approach with a case study strategy. The subjects of this research were determined using purposive sampling approach, involving 5 informants as personnel in each cost pool. In-depth interviews and documentation of internal financial data were used as data collection techniques. The results of this study show the presence of inefficiency in the Accommodation cost pool and the Cleaning service cost pool. Inefficiency in cesarean surgery services can be determined after analyzing the utilization of capacity, which is the end result of cost calculation using the TDABC method. The stages of cost analysis using the TDABC method in this study include: 1) Identification of Cost Pools, 2) Identification of total costs for each cost pool, 3) Determination of practical capacity and capacity cost rate for each cost pool, 4) Determination of time estimates for each cost pool, 5) Cost calculation, and 6) Analysis of capacity utilization to determine the level of inefficiency by calculating the percentage of available capacity compared to idle capacity. The results of this study are expected to provide input regarding the optimization of idle capacity, cost efficiency, and improvement of healthcare service processes in the hospital.